Determination of Organizational Resilience: Entrepreneurial Orientation Moderation of Government Policy on Tourism in Jambi Province - Haryono, Gampo; Lova, Anggil Nopra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the influence of entrepreneurial orientation on the resilience of tourism village actors in Jambi Province mediated by government policies. Respondents in this study were tourism actors consisting of tourism owners and managers in Jambi Province. The total number of respondents was 240 respondents. To find out whether the model created based on observation data was carried out using SEM-PLS. The results of this study found that Entrepreneurial Orientation and partial government policies have a significant influence on resilience, government policies also have a significant influence on the resilience of Tourism Village Actors in Jambi Province. Through harmonious collaboration between tourism actors and the government, a strong and sustainable tourism ecosystem can be created. This collaboration will help tourism actors in overcoming various dynamic challenges and support improving their welfare in the future.